A compatibility study of a secondary amine active pharmaceutical ingredient with starch: Identification of a novel degradant formed between desloratadine and a starch impurity using LC–MSn and NMR spectroscopy. Issue 2 (14th December 2012) - Yu, Xin; Buevich, Alexei V.; Li, Min; Wang, Xin; Rustum, Abu M.
Abstract Active pharmaceutical ingredients (APIs) containing primary and secondary amine moieties have been extensively studied for their potential incompatibility with monosaccharides and disaccharides containing a reducing end such as glucose, lactose, and maltose because of the undesirable interaction between the amine and aldehyde functionalities. Compatibility studies of these APIs with olysaccharides such as starch are much less common. During a recent compatibility study between starch and desloratadine, an API that contains a secondary amine functional group, we observed a novel degradant formed between desloratadine and a previously unidentified starch impurity in addition to an Amadori degradant formed between desloratadine and maltose, a known starch impurity. An approach that combines liquid chromatography–tandem mass spectrometry (LC–MSn) analysis, stress studies, and comprehensive nuclear magnetic resonance (NMR) analyses was used to identify this novel degradant. On the basis of the structure determined by NMR spectroscopy and the results from the stress studies, a degradation mechanism is proposed to account for the formation of this novel degradant through the reaction of desloratadine with an isomer of acetylformoin, an impurity of polysaccharide origin. Because starch is a very common excipient used in solid dosage formulations, the results of this compatibility study should facilitate pharmaceutical development involving secondary amine APIs and starch. © 2012 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:717–731, 2013